EXPERIENCE 2500 IMPLANTATION OF PENILE SEMI-RIGIDITY PROSTHESES FOR ERECTILE DYSFUNCTION - M. I. Kogan; V. V. Krasulin; D. V. Sizyakin; A. V. Shangichev; V. V. Gluhov (Вестник урологии, 2013)
The results of 2500 implantations we have developed semi-rigid prostheses, made between 1981 and 2013. Demonstrated surgical technique, its high efficacy in the treatment of erectile dysfunction resistant to drug therapy, and the low rate of postoperative complications.